PENGARUH NAUNGAN DAN JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL JAHE PADA LAHAN GAMBUT - Hazizah, Hazizah; Radian, Radian; Wasi’an , Wasi’an (Politeknik Negeri Ketapang, 2021)
Ginger require various types of nutrients in sufficient quantities for growth and development, both classified as macro and micro nutrients. Plant growth and development is based on various factors including soil factors and environmental factors (light intensity). Peat soils have a low fertility rate, characterized by low macro and micro nutrient content. This study aims to find the best type of dung, the best shade rate and interaction between shade rate and type of dung on ginger growth and yield in peatlands. This study uses a split plot design. As the main plot is the shade rate (N) consists of 6 levels of composition and Type of dung (P) as a subplot which consists of 3 levels of maintenance. Each combination was repeated three times with 6 plant samples each bed. The treatments were: shade rate factor (N) consisted of: n1 = 50% shade, n2 = 60% shade, n3 = 70% shade, n4= 80% shade, n5 = 90% shade, n6 = 100% shade. The second factor is type of dung (P) consisting of p1 = cow dung, p2 = chicken dung, p3 = goat dung. The results showed that shade rate only had a significant effect on plant height at 1 month after plant, and type of dung only had a significant effect on plant dry weight at 4 and 5 months after plant. There was no interaction between shade rate and type of dung in all monitoring observational variables.